Reward satisfaction and leadership satisfaction among Tamil primary school teachers in Melaka, Malaysia - Madhawa Nair, Subadrah; Balakrishnan, Gunasundari; Krishnasamy, Hariharan N; Singh, Gurdip Kaur Saminder; Siddique, Muhammad (Edelweiss Applied Science and Technology, 2024)
Analyzing the relationship between leadership satisfaction and reward satisfaction in primary schools can offer valuable insights for enhancing management and performance. This study aims to determine if there are significant differences in reward satisfaction and leadership satisfaction among Tamil primary school teachers in Melaka, based on their gender and teaching experience. The study adopted a descriptive research design. Stratified random sampling was employed in choosing 60 Tamil Primary School teachers in Melaka as a sample. This study used Leadership Satisfaction and Rewards Satisfaction Questionnaire (LRSQ) as instruments to collect the data. A pilot test was conducted among 30 randomly selected teachers to obtain the reliability of the instrument. The findings of the pilot test showed that the instrument is highly reliable and can be used for data collection. The key findings of the study revealed, that the reward as well as the leadership satisfaction of the male teachers were significantly higher than those of their female counterparts. On the other hand, there is no significant difference between senior teachers and junior teachers in the area of reward satisfaction. Similarly, the findings also indicated that the leadership satisfaction of the senior teachers is significantly higher than those of the junior teachers. This study has crucial pedagogical and practical implications because leadership and reward satisfaction can effect teachers’ performance in schools.